STUDI PENURUNAN PARAMETER BOD, COD DAN BOD/COD MENGGUNAKAN GABUNGAN VERTICAL ROUGHING FILTER DAN HORIZONTAL ROUGHING FILTER PADA LIMBAH CAIR DOMESTIK ARTIFICIAL - Flora Resti Utami; Ganjar Samudro; Sri Sumiyati (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
ABSTRACTDomestic wastewater treatment is necessary given the high levels of pollutants such as BOD and COD content. In Indonesia there have been domestic wastewater treatment technology but the application is not yet efficient enough, India and African implement a technology that is roughing filter water treatment using filtration mechanism. This study aims to determine the reduction in BOD, COD and BOD / COD using a combination of vertical roughing filters (VRF) and horizontal roughing filter (HRF) in domestic wastewater. This study uses VRF and HRF series of three variations of flow of 277.7 ml/h, 138.8 ml/h and 92.5 ml/h, three variations of the filter media size, coarse with diametres Ɵ20mm, Ɵ15mm, Ɵ10mm , medium size Ɵ15mm, Ɵ10mm, Ɵ6mm and fine size Ɵ10mm, Ɵ 6mm, Ɵ3mm and two variations of types filter media are gravel and charcoal. From research result obtained a removal parameters of BOD and COD optimum flow variation are 277.7 ml/h for the BOD by 90% eficiency and the variation of flow 138.8 ml/h for removals parameters COD by eficiency 99 %. Variations of filter media types for the removal parameters BOD and COD is gravel, while the optimum filter media size for the parameters BOD is coarse and optimum filter media size for COD is medium.